Effect of Sustainability Claim on Willingness to Pay for Upcycled Food in Digital Era: Differential Effect of Sustainability Claim Between Virtue and Vice Product Category - Ghazanfar, Sidra; Abdullah, Muhammad; Ummar, Rakhshan; Shabbir, Rizwan; Saqib, Shahnawaz (Frontiers in Environmental Science, 2022)
The growing demand for food availability is persuading researchers, marketers, and consumers to opt for various solutions that could ensure food sustainability for our upcoming generations. Upcycled food is one of the solutions which could lead to food sustainability by upcycling discarded food ingredients. However, marketers seem less interested in producing upcycled food because of their low acceptance and willingness to pay. This study investigated when sustainability claims prompt premium prices for upcycled food; whether it varies between virtue and vice product category?. The research incorporates two experiments on the willingness to pay for upcycled food and examines the role of the intervention product category (virtue vs vice). Overall, the results confirm the original findings; however, some differences in the context of virtue vs vice product categories have been observed. The results (study I, without sustainability claim) indicated that consumers showed more willingness to pay for conventional (virtue, vice) products as compared to upcycled (virtue, vice) products. The results further revealed that willingness to pay for vice products was low compared to virtue products, particularly for upcycled vice products. The findings of Study II indicated that sustainability claim increases the willingness to pay for upcycled food, both for virtue and vice product categories. However, willingness to pay for upcycled vice products increases more than for upcycled virtue products.